Impact on operative outcomes of laparoscopic simultaneous resection of colorectal cancer and synchronous liver metastases. Issue 1 (3rd April 2020) - Kawakatsu, Shoji; Ishizawa, Takeaki; Fujimoto, Yoshiya; Oba, Atsushi; Mise, Yoshihiro; Inoue, Yousuke; Ito, Hiromichi; Takahashi, Yu; Ueno, Masashi; Saiura, Akio
Abstract: Introduction: The efficacy of laparoscopic simultaneous resection of primary colorectal cancer and synchronous colorectal liver metastases (SCRLM) remains unclear. Methods: We retrospectively evaluated data from 258 patients who had undergone simultaneous curative resection of the primary tumor and SCRLM from 2006 to 2017. We compared surgical outcomes between open, hybrid (laparoscopic colorectal resection and open hepatectomy), and pure laparoscopic approaches. Surgical outcomes were also evaluated between the open hepatectomy (OH) group (ie, open/hybrid surgery) and the laparoscopic hepatectomy (LH) group (ie, pure laparoscopic surgery) in 141 patients later in the study period (2013‐2017), when the clinical indications for laparoscopic hepatectomy were restricted to simple wedge resection and/or left lateral sectionectomy in our center. Results: The pure laparoscopic approach was associated with significantly less intraoperative blood loss and a significantly shorter postoperative hospital stay than the open and hybrid approaches. Late in the study period, operative outcomes in the LH group (n = 37) were more favorable than for the OH group (n = 104) in terms of intraoperative blood loss and postoperative hospital stay. In patients with rectal cancer, however, earlier postoperative recovery in the LH group did not differ significantly from the OH group. Conclusion: Laparoscopic simultaneous resection of SCRLM with the primary tumor by simple hepatectomy is safe and may enhance patients' postoperative recovery, especially in patients with colon cancer.